Target Inhibition of CBP Induced Cell Senescence in BCR-ABL- T315I Mutant Chronic Myeloid Leukemia - Yang, Ke; Wang, Fang; Zhang, Hong; Wang, Xiaokun; Chen, Likun; Su, Xiaodong; Wu, Xingping; Han, Qianqian; Chen, Zhen; Chen, Zhe-Sheng; Fu, Liwu (Frontiers in Oncology, 2021)
The treatment of chronic myeloid leukemia (CML) with BCR-ABL tyrosine kinase inhibitors (TKIs), such as imatinib, has yielded clinical success. However, the direct targeting of BCR-ABL does not eradicate CML cells expressing mutant BCR-ABL, especially the T315I mutation in BCR-ABL. Moreover, increasing mutations were identified in BCR-ABL domain, resulting in TKIs resistance recently. It is necessary to find BCR-ABL-independent target for treating CML patients with various mutations, including T315I mutation in BCR-ABL. The dichotomous behavior of CREB binding protein (CBP) and E1A protein (p300), recruited by β-catenin associated with self-renewal and differentiation, have been identified in hematopoietic stem cells, respectively. In this study, CBP was aberrantly expressed in CML cells on the basis of Oncomine dataset. The β-catenin recruited much more CBP than p300 in CML cells. Down-regulation of CBP inhibited cell proliferation capacity and increased the binding of β-catenin to p300, thus promoting cell differentiation and p53-dependent cell senescence in CML cells with either wild type or T315I mutant BCR-ABL in vitro and in vivo models. These demonstrate CBP blockage can be developed for the treatment of CML independent of BCR-ABL mutation status including T315I.